Chisel: A Policy-Driven, Context-Aware, Dynamic Adaptation Framework - CAHILL, VINNY; KEENEY, JOHN (IEEE Computer Society, 2003)
We argue that the software user, the developer, the designer and indeed the application logic itself all possess invaluable intelligence to gear how software should adapt itself to changing requirements and changing context. We present Chisel, an open framework for dynamic adaptation of services using reflection in a policy-driven, context-aware manner. The system is based on decomposing the particular aspects of a service object that do not provide its core functionality into multiple possible behaviours. As the execution environment, user context and application context change, the service object will be adapted to use different behaviours, driven by a human-readable declarative adaptation policy script. To demonstrate this framework we will provide a dynamically adaptive middleware for mobile computing. The framework will allow users and applications to make mobile-aware dynamic changes to the behaviour of various services of the middleware, and allow the addition of new unanticipated behaviours at run-time, without changing or stopping the middleware or an application that may be using it. This is achieved by implementing the behaviours as metatypes in Iguana/J, which supports non-invasive dynamic associations of metatypes to service objects without any requirement to interrupt, change or access the object?s source code.
Fourth IEEE International Workshop on Policies for Distributed Systems and Networks (POLICY 2003)
PUBLISHED
Lake Como, Italy
Keywords: Computer Science